2019
DOI: 10.1097/psy.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Depression in the Years After Heart Transplantation for Mortality During Long-Term Follow-Up

Abstract: Objective: Current understanding of the prognostic impact of depression on mortality after heart transplantation (HTx) is limited. We examined whether depression after HTx is a predictor of mortality during extended follow-up. Subsequently, we explored whether different symptom dimensions of depression could be identified, and whether they were differentially associated with mortality. Methods: Survival analyses were performed in a sample of 141 HTx recipients assessed for depression, measured by self-report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…Our observation that heart transplant recipients with depression within the first year had decreased survival up to 5 years post‐transplant is congruent with other studies 9,13 . After adjustment, this relationship was no longer significant suggesting an associative rather than causative relationship.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observation that heart transplant recipients with depression within the first year had decreased survival up to 5 years post‐transplant is congruent with other studies 9,13 . After adjustment, this relationship was no longer significant suggesting an associative rather than causative relationship.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between depression and post‐transplant clinical characteristics and outcomes is not well understood. Depression either pre‐ or post‐heart transplantation may be associated with a greater degree of medication nonadherence and post‐transplant hospitalization and in some studies, increased mortality 5‐9 …”
Section: Introductionmentioning
confidence: 99%
“…26 Some evidence also suggests that depression is associated with poor outcomes after heart transplantation. 27 Besides, different case-control studies showed that HF is associated with an increased risk of suicide, especially during the first 6 months and up to 2 years after HF diagnosis. 28 This suicide risk is influenced by depressive symptoms.…”
Section: Depression In Heart Failurementioning
confidence: 99%
“…Details on recruitment procedures as well as a variety of results of cross-sectional and longitudinal studies of this cohort have been published earlier. 3,[16][17][18] All patients received immunosuppressive therapy according to local protocol.…”
Section: Study Samplementioning
confidence: 99%
“…2,3 Both biological and behavioral mechanisms have been discussed as underlying factors for this association. 3 In contrast, data on the association of anxious symptomatology with survival after HTx are still sparse and contradictory, 4-10 with only three studies specifically examining the association of posttransplant anxious symptomatology with survival after HTx. 4,8,9 The authors of a meta-analysis published in 2015, deemed it premature to draw strong conclusions…”
mentioning
confidence: 99%